Sex Differences in Autophagy Contribute to Female Vulnerability in Alzheimer's Disease - Congdon, Erin E. (Frontiers in Neuroscience, 2018)
Alzheimer’s disease (AD) is the most common form of dementia, with over 5.4 million cases in the US alone (Alzheimer's Association, 2016). Clinically, AD is defined by the presence of plaques composed of A and neurofibrillary pathology composed of the microtubule associated protein tau. Another key feature is the dysregulation of autophagy at key steps in the pathway. In AD, disrupted autophagy contributes to disease progression through the failure to clear pathological protein aggregates, insulin resistance, and its role in the synthesis of A. Like many psychiatric and neurodegenerative diseases, the risk of developing AD, and disease course are dependent on the sex of the patient. One potential mechanism through which these differences occur, is the effects of sex hormones on autophagy. In women, the loss of hormones with menopause presents both a risk factor for developing AD, and an obvious example of where sex differences in AD can stem from. However, because AD pathology can begin decades before menopause, this does not provide the full answer. We propose that sex-based differences in autophagy regulation during the lifespan contribute to the increased risk of AD, and greater severity of pathology seen in women.